Chemokines sound the alarmin: The role of atypical chemokine in inflammation and cancer. (August 2018) - Borroni, Elena Monica; Savino, Benedetta; Bonecchi, Raffaella; Locati, Massimo
Highlights: During inflammatory reactions, chemokines are tissue-derived signals serving as alarmins in case ot tissue damage. Atypical chemokine receptors control chemokine bioavailability in tissues by presentation, transport and degradation processes. Atypical chemokine receptors activities are essential for control of immune responses to tissue damage and in tumor biology. Abstract: As main drivers of leukocyte recruitment during inflammatory reactions, chemokines act as mediatrs of alarmins in priming host defense responses after tissue exposure to toxic or infectious agents, immunomediated damage, and in inflammation-driven tumors. Chemokines can therefore be considered alarm signals generated by tissues in a broad number of conditions, and mechanisms controlling chemokines biological activities are therefore key to regulate tissue reactions induced by alarmins. By transporting, presenting or scavenging different sets of chemokines, atypical chemokine receptors represent an emerign subfamily of chemokine receptors which operates in tissues as chemokine gatekeepers in order to establish and shape their gradients and coordinate leukocyte recruitment.